A robust incubator to improve access to microbiological culture in low resource environments - Miller, A; Ghionea, S; Vongsouvath, M; Davong, V; Mayxay, M; Somoskovi, A; Newton, P; Bell, D; Friend, M (American Society of Mechanical Engineers, 2019)
To help address the limitations of operating conventional microbiological culture incubators in low resource environments, a new incubator design was developed and tested to meet the requirements of operation in laboratories without reliable power (power outages up to 12 contiguous hours) or climate control (ambient indoor temperatures from 5 °C to 45 °C). The device is designed to enable adherence to incubation temperatures recommended for growth detection, identification, and drug susceptibility testing (DST) of human pathogenic bacteria. During power outages, stable temperatures are maintained in the device's internal sample compartment by employing phase change material (PCM) as a bi-directional thermal battery to maintain incubation temperature. Five prototypes were tested in a laboratory setting using environmental test chambers and programmable power supplies, and three were field tested in the Lao PDR in situations of intended use. The prototypes successfully held their temperature to within 61 C in both laboratory environmental chamber testing as well as during the field test. The results indicate that the device will maintain stable culture temperatures across periods of intermittent power supply, while enabling normal workflow of this could greatly increase the availability of microbiological culture for diagnosis and antimicrobial resistance (AMR) monitoring.